A substance use relapse prevention programme for youth with substance use problems in Botswana - Wada Gaolaolwe; Miriam M. Moagi; Gaotswake P. Kovane; Leepile A. Sehularo (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Substance use relapse among the youth is a worldwide concern with negative ramifications on their lives, families, communities and nations at large.